2019
DOI: 10.1101/641506
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

High-resolution and High-accuracy Topographic and Transcriptional Maps of the Nucleosome Barrier

Abstract: Nucleosomes represent mechanical and energetic barriers that RNA Polymerase II (Pol II) must overcome during transcription. A high-resolution description of the barrier topography, its modulation by epigenetic modifications, and their effects on Pol II nucleosome crossing dynamics, is still missing. Here, we obtain topographic and transcriptional (Pol II residence time) maps of canonical, H2A.Z, and monoubiquitinated H2B (uH2B) nucleosomes at near base-pair resolution and accuracy. Pol II crossing dynamics are… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 59 publications
2
9
0
Order By: Relevance
“…Thus, Rpb4 prevents Pol II from pausing at the 3' regions of genes that may protect from premature termination before the canonical 3' cleavage site is transcribed. Similarly, more 3' pause sites are found in the ubp8∆ strain, consistent with the global increase in this strain of H2B ubiquidylation, a mark that increases the nucleosomal barrier to Pol II and is coincident with Pol II pausing at transcription termination sites (Bonnet et al, 2014;Chen et al, 2019;Harlen et al, 2016). Together, these data show how the chromatin landscape and transcriptional regulatory network of the cell dictate sites of Pol II pausing that in turn controls where and for how long Pol II pauses during elongation.…”
Section: Figure S5csupporting
confidence: 79%
See 1 more Smart Citation
“…Thus, Rpb4 prevents Pol II from pausing at the 3' regions of genes that may protect from premature termination before the canonical 3' cleavage site is transcribed. Similarly, more 3' pause sites are found in the ubp8∆ strain, consistent with the global increase in this strain of H2B ubiquidylation, a mark that increases the nucleosomal barrier to Pol II and is coincident with Pol II pausing at transcription termination sites (Bonnet et al, 2014;Chen et al, 2019;Harlen et al, 2016). Together, these data show how the chromatin landscape and transcriptional regulatory network of the cell dictate sites of Pol II pausing that in turn controls where and for how long Pol II pauses during elongation.…”
Section: Figure S5csupporting
confidence: 79%
“…dst1∆ pause sites clustered far away from those in wild-type cells, consistent with the backtracking role of Dst1 that leads to downstream-shifted pause sites (Churchman and Weissman, 2011;Noe Gonzalez et al, 2021). H2B ubiquitidation increases the nucleosomal barrier to Pol II (Chen et al, 2019), so alterations to histone ubiquitination might lead to new pause sites. Interestingly, pause sites after the loss of Rad6, Ubp8, Paf1 and Cdc73 all cluster together.…”
Section: Figure S5csupporting
confidence: 60%
“…H2A.Z.1 also regulates the negative elongation factor (NELF) turnover and the reloading of the preinitiation complex [57]. This robust study combining genomic techniques and live cell high-resolution microscopy supports that H2A.Z.1 slows RNAPII pause-release rate and is further supported by biophysical data that H2A.Z nucleosome widens the transcriptional barrier and lengthens the crossing of RNAPII compared with canonical nucleosomes [62].…”
Section: Role In Gene Transcriptionmentioning
confidence: 65%
“…In this section, we will explore the emerging functions in transcriptional regulation associated directly with H2A.Z. The role of H2A.Z in RNA polymerase II (RNAPII) pausing and elongation It has been suggested that H2A.Z plays a critical role in RNAPII initiation and elongation; however, opposing results are also reported (Figure 3) [57,[59][60][61][62]. After RNAPII enters early elongation, it pauses about 20-60 bp downstream from the TSS; this 'pausing' effect is increasingly recognised as an important step in regulating gene expression [63].…”
Section: Role In Gene Transcriptionmentioning
confidence: 99%
“…Passage of Pol II is nevertheless possible because of transient unwrapping of DNA at the ends of the nucleosome (Polach and Widom, 1995;Prunell and Kornberg, 1978); the transcribing polymerase invades an unwrapped end and proceeds, by successive unwrapping events, through the nucleosome. Passage of Pol II is able to fully displace the nucleosome (Lorch et al, 1987;Kulaeva et al, 2013;Chen et al, 2019).…”
mentioning
confidence: 99%